Tubuh dan Politik: Perspektif Feminis Iris Marion Young: - - Laku, Silvester Kanisius (Universitas Katolik Parahyangan, 2023)
This article explores the thoughts of one of contemporary feminist political figures, Iris Marion Young of the body, as well analyzing the dynamics of power, inequality, and experiences of social, cultural, and political alienation. Young states that the body transcends its physicality, it emerges as a locus of politics. Power, he says, operates on the body through social norms, cultural expectations, and policies, shaping the way individuals understand and experience their bodies. These norms, depicted as sources of inequality in bodily experience, contribute to the establishment of socio-political hierarchies in society. Understanding the potential and capacity of the body has a significant political influence in determining the existence of women within the framework of society. This paper aims to describe and analyze Young's concept of feminist politics and highlight its political implications regarding the role of women in society. This research begins with the assumption that, through self-transcendence and understanding the body's capacity to resist immanence, women can assert their existence in society. Rooted in the belief that, as political subjects, all humans are inherently equal, Young challenges traditional paradigms of social and political roles, offering a radical perspective on the body and the self-empowering capacity to live with others. To achieve this goal, the author uses a literature review methodology, emphasizing elements of philosophical research methods such as hermeneutics, description, inductive and deductive analysis, as well as analysis of the coherence of Young's ideas. This article contributes to the ongoing discourse on feminist philosophy, offering a comprehensive exploration of Young's influential thinking on the political dimensions of the body and its implications for women's roles in society.